Refocusing on sexually transmitted infections (STIs) to improve reproductive health: a call to further action - Otu, Akaninyene; Danhoundo, Georges; Toskin, Igor (BioMed Central (BMC) - Springer Nature, 2021)
The current state of sexually transmitted infections (STIs). STIs are infections that result from the transmission of a pathogenic organism by sexual contact . Globally, STIs constitute a major burden and a significant public health challenge, driven by health systems challenges related to inadequately resourced, poor-quality services on the one hand and social stigma and discrimination surrounding STIs on the other, which together discourage many people from seeking and receiving services (i.e., counselling, testing, and treatment) The World Health Organization (WHO) estimated that in 2016 the global annual incidence of four of the eight most prevalent STIs (i.e. chlamydia, gonorrhea, trichomoniasis and syphilis) among people 15–49 years of age was 376.4 million infections. These four infections are curable, unlike viral infections such as HIV, hepatitis B, herpes simplex virus (HSV) and human papillomavirus (HPV), requiring long term management and treatment
Keywords: Veloshnee Govender; Sanni Yaya; ACE: Reproductive Health Innovation; Nigeria; University of Benin; CERHI; Reproductive Health; Sexual Health; World Health Organization; United Nations Population Fund (UNFPA); Sexual transmitted Infections (STIs)